Evaluating the influence of connectivity and distance on biogeographical patterns in the south‐western deserts of North America. (3rd March 2016) - Van Dam, Matthew H.; Matzke, Nicholas J.
Abstract: Aim: To examine the role of geological history, connectivity and distance in shaping the biogeographical structure of North American desert clades that are restricted to habitat islands (sand dunes and relictual aquatic habitats), using statistical model choice on old and new probabilistic biogeographical models. Location: North America, Mojave, Sonoran and Chihuahuan Deserts. Materials and methods: Dated phylogenies were estimated for three field‐sampled insect clades ( Trigonoscuta, Rhaphiomidas and sand treader crickets), and five other literature‐sampled clades (the snails Assiminea, Pyrgulopsis and Tryonia ; the desert fringe‐toed lizard Uma ; and the desert pupfish Cyprinodon ).BioGeo BEARS was used to statistically compare biogeographical models assuming unconstrained or connectivity‐constrained dispersal, with or without founder‐event speciation (jump dispersal) permitted. Finally, we introduce and test a novel distance‐based dispersal model (+x) where dispersal probability is multiplied by distance to the power x . Results: We observed little concordance between biogeographical patterns and timing of geological events. Model comparisons were decidedly in favour of inclusion of founder‐event speciation in the models for most taxa, with only a small taxon, Uma, showing support for the model favouring vicariance. The inclusion of a constrained‐dispersal matrix was favoured by three of the eight taxa examined ( Cyprinodon, sand treader crickets, and Trigonoscuta ). Surprisingly, tests for distance influencing dispersal probability were mostly negative. Main conclusions: Our results do not show support for any one geological event shaping the biogeographical patterns of these desert taxa. Instead, the histories of desert dune and aquatic taxa are largely products of rare jump dispersal events, and can be considered island‐like systems. Although results are negative for the distance‐based dispersal model, this in itself demonstrates the superiority of explicit statistical model testing over a priori assumption of fixed models in historical biogeography.